Science and code validation program to secure ignition on LMJ. (March 2016) - Lefebvre, E; Boniface, C.; Bonnefille, M.; Casner, A.; Esnault, C.; Galmiche, D.; Gauthier, P.; Girard, F.; Gisbert, R.; Leidinger, J.-P.; Loiseau, P.; Masse, L.; et al.
Abstract: The CEA/DAM ICF experimental program is currently conducted on LIL and Omega with the goal of improving our simulation tool, the FCI2 code. In this effort, we focus on typical ICF observables: hohlraum radiation drive history, capsule core shape and neutron emission history, hydrodynamic instability growth. In addition to integrated experiment, specific designs are also helpful to pinpoint a particular phenomenon. In this article, we review our current efforts and status, and our future projects on Omega and LMJ.